2018
DOI: 10.1016/j.jechem.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Path towards high-efficient kesterite solar cells

Abstract: Kesterite structure semiconductor Cu 2 ZnSn(S,Se) 4 is one of the most promising candidate as a light absorber material to overtake the next generation of thin film solar cells, owing to its low cost, non-toxic, and earth abundant source materials. The Shockley-Queisser limit of the single junction Cu 2 ZnSn(S,Se) 4 solar cell is over 30%, signifying a large potential of this family of solar cells. In the past years, with the development of synthesis techniques, Cu 2 ZnSn(S,Se) 4 solar cells have attracted con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 141 publications
1
30
0
2
Order By: Relevance
“…Thin film solar cells Cu 2 ZnSnS 4 (CZTS) and Cu 2 ZnSnSe 4 (CZTSe) are prospective substitutes for Cu(In,Ga)Se 2 (CIGS) due to the composition elements of their absorber materials are non‐toxic and earth abundant. Up to now, the champion efficiency of CZTSSe solar cells is still 12.6%, which is mainly because of the large V OC deficit ( E g / q ‐ V OC ) . One of the important factors for low efficiency in CZTSSe is cationic disorder .…”
Section: Introductionmentioning
confidence: 99%
“…Thin film solar cells Cu 2 ZnSnS 4 (CZTS) and Cu 2 ZnSnSe 4 (CZTSe) are prospective substitutes for Cu(In,Ga)Se 2 (CIGS) due to the composition elements of their absorber materials are non‐toxic and earth abundant. Up to now, the champion efficiency of CZTSSe solar cells is still 12.6%, which is mainly because of the large V OC deficit ( E g / q ‐ V OC ) . One of the important factors for low efficiency in CZTSSe is cationic disorder .…”
Section: Introductionmentioning
confidence: 99%
“…Kesterite‐structured Cu 2 ZnSn(S,Se) 4 (CZTSSe) has been studied extensively because of its earth‐abundance, low toxicity, and high absorption coefficient . To date, the efficiency of CZTSSe solar cells has reached 12.7%, which is still far lower than the best efficiency of CIGS solar cells (22.9%) .…”
Section: Introductionmentioning
confidence: 99%
“…Reviews can be found on fabricating nanoparticles (NPs) of various types (e.g. metallic, chalcogenides, oxides) for application in different locations of thin-film photovoltaic devices [55], on the approach of using sintered NPs for CIGS or CZTS [56], and on the evolution of NP-based CZTS device efficiency [57]. Here, we provide an update and comprehensive survey on the CZTS nanoparticle processing.…”
Section: Nanoparticle-inksmentioning
confidence: 99%